Jezikovne izbire pri upovedovanju zaupnih virov informacij - Kalin Golob, Monika (Teorija in praksa, 2015)
The article discusses references to confidential sources of information in journalism using already affirmed phrases, so-called automatisms. The findings of the analysis of Slovenian 19th century newspapers are supplemented with information on the contemporary use of automatisms, as confirmed with in-depth interviews by journalists themselves and shown by analysis of the newspaper part of the Gigafida corpus, a reference corpus of Slovenian (for the period 2000-2009). Among other things, we found that several forms of reference automatism from a reliable source (we learnt) have formed part of Slovenian news reporting for almost 150 years and that, in the last decade, two automatisms have mostly been used, i.e. according to our information and according to unofficial information. Surprisingly, the automatism rumour has it is very common as well.
Keywords: časnikarski jezik; Jezik (Jezikoslovje); Journalism; Language; Novinarstvo; sklicevalni avtomatizmi; Slovenia; Slovenija; Stilistika; Stylistics